Scoping Review on the Licensure Examination for Teachers (LET) in the Philippines - Joy A. Bellen; Jose Celso S. Perez; Arlee Jen C. Avellana; Andrea Marie F. Borneo (International Journal of Evaluation and Research in Education (IJERE), 2022)
The purpose of the licensure examination is to determine who among the examinees are equipped with the minimum knowledge or expertise to carry out the functions of a teacher competently. While studies on licensure examination for teachers are available, synthesis using scoping reviews has not yet been conducted. Using Arksey and O’Malley’s (2005) scoping review framework, results indicate that 1) descriptive-correlational and documentary analysis methodologies were commonly used, 2) the trends in the scope focus on finding the relationship or correlation of potential predictive factors of the performance of BEEd graduates or both BEEd and BSEd graduates with emphasis, 3) the bulk of the research focuses on academic achievement, and 4) studies identified suggestion to boost licensure performance of the TEIs. Recommendations from the articles are discussed.